Effects of Traditional Chinese Fitness Exercises on Negative Emotions and Sleep Disorders in College Students: A Systematic Review and Meta-Analysis - Yang, Tingting; Guo, Yingjie; Cheng, Yang; Zhang, Yue (Frontiers in Psychology, 2022)
Background: The purpose of this study was to systematically review the effectiveness of regular traditional Chinese fitness exercises on negative emotions and sleep disorders in college students, and to provide evidence-based evidence and new ideas for the negative emotions and sleep disorders among college students. Methods: A systematic search using five English (PubMed, Embase, Scopus, EBSCO, the Cochrane Library) and four Chinese (CNKI, Wan Fang, VIP, CBM) databases were initiated to identify randomized controlled trials (RCT) assessing the effect of traditional Chinese fitness exercises on negative emotions and sleep disorders among college students. Standardized mean differences (SMD) and their 95% confidence intervals (CI) were used to determine the pooled effect of the intervention. The Cochrane bias risk assessment tool was used to evaluate the methodological quality and the data were analyzed with Review Manager 5.4. Results: A total of 12 RCTs were included, including 1052 subjects. The results showed a potential beneficial effect of traditional Chinese fitness exercises on reducing depression (SMD =-0.93, 95 %CI [- 1.76, -0. 10]), anxiety (SMD=-0.74, 95 % CI [-0.93, -0.54]) and the sleep disorders (SMD=-2.77, 95% CI [-4.57, -0.97]) symptoms, and these effects were better than in the control group. Conclusion: The findings of this review suggested traditional Chinese fitness exercises could improve both the negative moods and sleep disorders Compared with that of healthy students, the effect on college students with mild to moderate psychological symptoms was obviously improved. The SCL-90 scale is better than the SDS scale in evaluating the improvement effect of traditional Chinese fitness exercises on depression. It was the best intervention program on negative emotions and sleep disorders among college students that the intervention duration was practiced over 5 sessions/week for 30-60 min/session for over 12 weeks.